Analysis of the Cochrane Review: Chromoscopy Versus Conventional Endoscopy for the Detection of Polyps in the Colon and Rectum. Cochrane Database Syst Rev. 2016;4:CD006439 - Libânio, Diogo (2016)
Although colonoscopy is considered the most accurate test for the investigation of colorectal polyps, lesions ≤ 10 mm may be missed in approximately 10%. Chromoscopy may increase the detection of colorectal polyps. A systematic review and meta-analysis was performed to investigate the benefit of cromoscopy in colorectal polyps detection. Seven randomized controlled trials were included (incuding 2,727 participants) comparing polyp detection (both neoplastic and non- neoplastic polyps) in patients submitted to conventional colonoscopy or colonoscopy with chromoscopy. Chromoscopy was associated with a significant improvement in all detection endpoints (number of polyps, number of neoplastic polyps, number of diminutive polyps, number of neoplastic diminutive polyps, proportion of patients with at least one polyp and proportion of patients with at least one neoplastic polyp). However, when highdefinition colonoscopes were used in the control group, chromoscopy benefit does not seem to be significant. Besides, routine use of chromoscopy may have implications in the accessibility of colonoscopy and in the effectiveness of screening programs. Moreover, the benefit of chromoscopy in the era of high-definition colonoscopy is questionable.